Mangol invasion of Eastern Europe In the thirteenth century AD - عباس رندة; معطية رشيدة (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The mangols Lived on the outskirts of the ancient world in the harsh plains and ravines, without knowing their Lives any mani Festation of civilization witnessed in that ear, until Tymogen (Genghis Khan), who tans formed the Mongols into amilitary Force in which they entered world history in their own way. After the unification of the Mongols by Genghis Khan who declared her ruler anew phase of Mongol history began, its main title was the wars of horrific massacres and the merciless fighting of the peoples they occupied, the Mongols were knew for their brutality and extreme cruelty, thus an empire of the mongols did not know history in its strength and papies anden the area of land they controlled and the peoples they ruled where this empire was in its, establisbment and expansion of the events, of third and fourteeth centuries AD, at present, the mangol Empire has become afertile material for seho lars and researchers to study the ihistory of this empire.